2021
DOI: 10.3389/falgy.2021.734733
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanisms of AERD—Recent Advances

Abstract: The pathomechanisms behind NSAID-exacerbated respiratory disease are complex and still largely unknown. They are presumed to involve genetic predisposition and environmental triggers that lead to dysregulation of fatty acid and lipid metabolism, altered cellular interactions involving transmetabolism, and continuous and chronic inflammation in the respiratory track. Here, we go through the recent advances on the topic and sum up the current understanding of the background of this illness that broadly effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…Finally, serum blood and sputum eosinophils correlated with each other and total serum IgE levels. Taken together, this part of our results corroborates the observations made by others in similar groups of patients [ 7 , 31 ], suggesting an overall high generalization potential of our findings, including those trying to answer scientific questions asked here for the first time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, serum blood and sputum eosinophils correlated with each other and total serum IgE levels. Taken together, this part of our results corroborates the observations made by others in similar groups of patients [ 7 , 31 ], suggesting an overall high generalization potential of our findings, including those trying to answer scientific questions asked here for the first time.…”
Section: Discussionsupporting
confidence: 93%
“…However, to validate the generalization potential of the main findings of t investigation, we first analyzed the relationships between the basic pathophysiologi parameters of AERD-related inflammation, such as involved immune cells, eicosano or IgE, and compared them to the previous observations by other researchers [7,31]. schematically illustrate this part of our results, shown in more detail in Figure 1 and Ta 2, Figure 4 was created, with eosinophil-neutrophil balance representing a cent reference line, to which all the other parameters relate.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the setting of ASA and NSAID ingestion, an increased ratio of AA is shunted toward the lipoxygenase pathway, causing an acute increase in pro-inflammatory leukotrienes with resultant bronchospasm, mucus production, eosinophil and leukocyte chemotaxis, vascular permeability, and platelet aggregation. [12][13][14] From a mechanistic standpoint, recent literature has shown that AERD patients exhibit an enhanced taste sensitivity to the bitter compound denatonium benzoate (DB). 15 Additionally, nasal polyps have been shown to exhibit an increased frequency of a unique cell type on the sinonasal epithelium called the solitary chemosensory cell (SCC) which expresses receptors sensitive to DB and is the exclusive epithelial source of interleukin (IL) 25.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the setting of ASA and NSAID ingestion, an increased ratio of AA is shunted toward the lipoxygenase pathway, causing an acute increase in pro-inflammatory leukotrienes with resultant bronchospasm, mucus production, eosinophil and leukocyte chemotaxis, vascular permeability, and platelet aggregation. 1214…”
Section: Introductionmentioning
confidence: 99%
“…Upon ingestion of NSAIDs inhibiting the cyclooxygenase-1 enzyme, N-ERD patients experience severe upper and lower respiratory tract symptoms. These are caused by dysregulation of the arachidonic acid metabolism with an overproduction of cysteinyl leukotrienes and prostaglandin D2 accompanied by decreased levels of the anti-inflammatory prostaglandin PGE 2 (7) .…”
Section: Introductionmentioning
confidence: 99%